Utilization of Classcraft in Developing Positive Student Behavior - Susila, I Komang Dedik (Journal of Education Technology, 2020)
Affective assessment in distance learning has a great challenge. One of the media that can be used as well as motivated students is ClassCraft. Meanwhile, some limited persons can implement this media. This research aimed at analyzing the procedures of usingClassCraftin developingstudents' positive attitudes. The research subject was a lecturer and students of English Language Education, Faculty of Teacher Training, Dwijendra University. This research was a descriptive qualitative study that elaborates the implementation of ClassCraft to develop a positive attitude. The data were collected through observation and interview using observation and interview guide. The data were analyzed using qualitative data analysis by Milles and Huberman (1994). The finding showed that the implementation of ClassCraft was implemented in three stages; planning, implementing, and evaluating. It can be a guidance of implementing ClassCraft in developing students' positive behaviors.